An investigation on surface generation in ultra-precision raster milling. (15th September 2011) - To, S.; Wang, S.J.
This paper studied the factors affecting surface roughness in ultra-precision raster milling (UPRM). Through the investigation on the surface generation mechanism, factors including cutting parameters, tool path generation (TPG) and tool geometry are taken into consideration. A series of cutting experiments is conducted to investigate the influences of three factors including feed direction, depth of cut and entry distance on surface roughness profiles and the surface quality of the ultra-precision raster milled surface. The results show that the surface finishing in horizontal cutting is better than that in vertical cutting and the surface roughness in UPRM can be minimised by selecting the optimal values of depth of cut and entry distance.